UNC-87 isoforms, Caenorhabditis elegans calponin-related proteins, interact with both actin and myosin and regulate actomyosin contractility - Ono, Kanako (Mol Biol Cell, 2015)
Calponin-related proteins are widely distributed among eukaryotes and involved in signaling and cytoskeletal regulation. Calponin-like (CLIK) repeat is an actin-binding motif found in the C-termini of vertebrate calponins. Although CLIK repeats stabilize actin filaments, other functions of these actin-binding motifs are unknown. The Caenorhabditis elegans unc-87 gene encodes actin-binding proteins with seven CLIK repeats. UNC-87 stabilizes actin filaments and is essential for maintenance of sarcomeric actin filaments in striated muscle. Here we show that two UNC-87 isoforms, UNC-87A and UNC-87B, are expressed in muscle and nonmuscle cells in a tissue-specific manner by two independent promoters and exhibit quantitatively different effects on both actin and myosin. Both UNC-87A and UNC-87B have seven CLIK repeats, but UNC-87A has an extra N-terminal extension of ∼190 amino acids. Both UNC-87 isoforms bind to actin filaments and myosin to induce ATP-resistant actomyosin bundles and inhibit actomyosin motility. UNC-87A with an N-terminal extension binds to actin and myosin more strongly than UNC-87B. UNC-87B is associated with actin filaments in nonstriated muscle in the somatic gonad, and an unc-87 mutation causes its excessive contraction, which is dependent on myosin. These results strongly suggest that proteins with CLIK repeats function as a negative regulator of actomyosin contractility.